2007
DOI: 10.2522/ptj.20070003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Instructors’ Perceptions of Behaviors That Comprise Entry-Level Clinical Performance in Physical Therapist Students: A Qualitative Study

Abstract: Participants reported evaluating students' performance based on attributes similar to those suggested by the American Physical Therapy Association's Physical Therapist Clinical Performance Instrument and previous research. However, subjectivity also was involved in their decision about whether students were able to practice at the entry level. Participants also concluded that entry-level students need not be independent in all clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 16 publications
1
30
0
5
Order By: Relevance
“…11 One way to provide support is through mentored independence, in which there is a balance between independence and the need for assistance. 20 As new clinicians gain more experience, they gain more independence.…”
Section: Gaps In Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…11 One way to provide support is through mentored independence, in which there is a balance between independence and the need for assistance. 20 As new clinicians gain more experience, they gain more independence.…”
Section: Gaps In Preparationmentioning
confidence: 99%
“…A study examining preceptors' expectations of new physical therapists found that confidence is very important for new physical therapists. 20 Regardless of a physical therapist's knowledge, if they did not display confidence, the patients would ''pick up on'' that and were less likely to listen to the physical therapist's recommendations than when a physical therapist displayed confidence. Similar to our findings, Carr and Volberding 6 found that confidence was a deficiency reported by new ATs.…”
Section: Shortcomingsmentioning
confidence: 99%
“…'gut feeling' seems to represent their cognitive integration of those characteristics into a decision about the overall adequacy of performance." 10 Cross and Hicks concluded that preceptors commonly use implicit criteria in the decision making process; preceptors would ask themselves if they would hire this student for their decision-making framework rather than use clinically-based objective measures. 11 Alexander's heuristic model found that preceptors assessed whether, in their opinion, the student's performance was representative of the desirable characteristics of an entry-level practitioner.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to be a life-long, self-directed learner is vital for health professionals, with clinicians now expecting new graduates to possess self-directed learner attributes [3].…”
Section: Introductionmentioning
confidence: 99%